Rupture of Ovarian Pregnancy in a Woman with Low Beta-hCG Levels - Serena Resta; Eliana Fuggetta; Federica D'Itri; Simona Evangelista; Adele Ticino; Maria Grazia Porpora (Hindawi Limited, 2012)
Background. Ovarian pregnancy is a rare form of ectopic pregnancy. It is often difficult to distinguish from tubal pregnancy, and diagnosis and management are frequently a challenge. Case. A 33-year-old nulligravida woman presented with light vaginal bleeding and bilateral lower quadrants abdominal pain. Beta-human chorionic gonadotropin (beta-hCG) level (592 mUI/mL) and clinical and ultrasound (US) findings were suspicious for tubal pregnancy. On the third day, despite beta-hCG decrease (364 mUI/mL), she complained of severe pain in the lower abdomen, and physical examination revealed abdominal rebound tenderness. US showed a large amount of fluid in the abdominal cavity. Because of the unstable clinical condition, emergency laparoscopy and resection of left ovarian ectopic pregnancy were performed. Histology confirmed ovarian gestation. Conclusion. This case shows that ectopic pregnancy rupture may occur despite low levels of beta-hCG. Hemoperitoneum is not contraindication to laparoscopy.